Pengaruh Customer Experience dan Customer Trust Terhadap Keputusan Pembelian Ulang Pada platform TikTok Shop - Rahma, Nuri Aulia; Asikin, Doni Dirgantara (Peneliti.net, 2025)
This study aims to determine the effect of customer experience and customer trust on repurchase decisions on the TikTok Shop platform, with a case study on students of the Faculty of Economics at Universitas Nasional Pasim Bandung. The background of this research is based on the increasing use of TikTok Shop as an online shopping platform that integrates entertainment with commercial transactions. The research method used is quantitative, with data collected through questionnaires distributed to 95 respondents. Data analysis was carried out using validity and reliability tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The results show that customer experience has a positive and significant effect on repurchase decisions, customer trust has a positive and significant effect on repurchase decisions, and simultaneously, customer experience and customer trust significantly influence repurchase decisions on the TikTok Shop platform. Thus, it can be concluded that the better the customer experience and trust in TikTok Shop, the higher the students’ intention to make repurchase decisions.